LEXICALIZATION WITHIN THE NOUN CATEGORY (International journal of artificial intelligence, 2026)
This article discusses the phenomenon of lexicalization in the Uzbek language, its formation, and in particular, the lexicalization of units related to nouns, and analyzes examples.